Design Features of a Removable Module for Securing Containers in Gondola Cars - Panchenko, S. V.; Lovska, A. O.; Pavliuchenkov, M. V.; Rukavishnykov, P. V. (Science and Transport Progress, 2024)
Purpose. The main purpose of the study is to highlight the design features of the design of a removable module for fastening containers in gondola cars. Methodology. For the safe transportation of containers in gondola cars, it is proposed to use a removable module. This module operates on the principle of an intermediate adapter between the container and the open wagon body. The choice of the profiles of the beams of the frame of the removable module was made according to the moments of resistance of their components. To do this, the core system of the removable module frame was constructed and calculated using the Lira CAD software package. According to the maximum bending moment acting in the module frame due to the moment of resistance and the known permissible stresses, the profile of the frame beams was selected. Taking into account the selected profile of the frame, its spatial model was built and strength calculations were performed. The finite element method implemented in SolidWorks Simulation was used for strength calculations. The calculation was carried out for two loading schemes of the removable module: the effect of a vertical load and the effect of vertical and longitudinal loads. Findings. Based on the calculation, the profile of the removable module was selected according to the determined value of the resistance moment - a square pipe with a height and width of 300 mm and a wall thickness of 5 mm. The results of the strength calculations of the removable module showed that for the case of its perception of a vertical load, the maximum stresses are 112.5 MPa. The maximum displacements occur in the upper parts of the superstructures and are about 1 mm. For the case of the vertical and longitudinal loads perceived by the removable module, the maximum stresses in its structure amounted to 287.6 MPa. The maximum displacements occurred in the end superstructure located on the side of the load applied to the removable module. These displacements amounted to 2.16 mm. Thus, the strength of the removable module for the considered loading schemes is ensured. Originality. A scientific approach to the design of a removable module for securing containers in gondola carsis proposed. Practical value. The research will contribute to the creation of recommendations for the design of modular-type vehicle structures, as well as to improving the efficiency of railway transport operation.